Calculations of the Evolution of the Ca L23 Fine Structure in Amorphous Calcium Carbonate. - Kahil, Keren; Raiteri, Paolo; Gale, Julian; Rez, Peter (2022)
Amorphous calcium carbonate (ACC) has been found in many different organisms. Biogenic ACC is frequently a precursor in the formation of calcite and aragonite. The process of structural transformation is therefore of great interest in the study of crystallization pathways in biomineralization. Changes in the prepeak/main peak (L2'/L2) intensity ratio of the Ca L23-edge X-ray absorption spectroscopy (XAS) of Ca-rich particles in skeleton-building cells of sea urchin larva revealed that ACC precipitates through a continuum of states rather than through abrupt phase transitions involving two distinct phases as formerly believed. Using an atomic multiplet code, we show that only a tetragonal or "umbrella-like" distortion of the Ca coordination polyhedron can give rise to the observed continuum of states. We also show on the basis of the structures obtained from previous molecular dynamics simulations of hydrated nanoparticles that the Ca L23-edge is not sensitive to atomic arrangements in the early stages of the transformation process.